2020
DOI: 10.1101/2020.11.04.20225417
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Th1 Dominant Nucleocapsid and Spike Antigen-Specific CD4+ and CD8+ Memory T Cell Recall Induced by hAd5 S-Fusion + N-ETSD Infection of Autologous Dendritic Cells from Patients Previously Infected with SARS-CoV-2

Abstract: To address the need for a safe, efficacious vaccine against SARS-CoV-2 infection with the critical properties of enabling both blocking viral entry into cells and clearing virus from cells already infected, we have developed a bivalent, human adenovirus serotype 5 (hAd5) SARS-CoV-2 S-Fusion + N-ETSD vaccine that is currently in clinical testing. This vaccine uses the next-generation hAd5 [E1-, E2b-, E3-] platform previously used successfully in cancer patients with pre-existing adenovirus immunity, engineered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 83 publications
(119 reference statements)
1
18
0
Order By: Relevance
“…Although not the subject of the investigation described here, we are developing a dual-antigen human adenovirus serotype 5 (Ad5) platform-based vaccine that delivers both a spike protein with a linker to increase cell surface expression and humoral responses (S-Fusion) and the highly antigenic and conserved nucleocapsid (N) protein with a signal sequence (an Enhanced T-cell Stimulation Domain, ETSD) to direct it to subcellular compartments that enhance MHC I and II responses 18 . It is our belief that the vaccine, hAd5 S-Fusion + N-ETSD, due to its ability to elicit cell-mediated in addition to humoral immune responses, as shown in both a rodent model 19 and non-human primates 20 , offers hope to those regions such as South Africa wherein dangerous variants of SARS-CoV-2 have swept the country.…”
Section: Discussionmentioning
confidence: 99%
“…Although not the subject of the investigation described here, we are developing a dual-antigen human adenovirus serotype 5 (Ad5) platform-based vaccine that delivers both a spike protein with a linker to increase cell surface expression and humoral responses (S-Fusion) and the highly antigenic and conserved nucleocapsid (N) protein with a signal sequence (an Enhanced T-cell Stimulation Domain, ETSD) to direct it to subcellular compartments that enhance MHC I and II responses 18 . It is our belief that the vaccine, hAd5 S-Fusion + N-ETSD, due to its ability to elicit cell-mediated in addition to humoral immune responses, as shown in both a rodent model 19 and non-human primates 20 , offers hope to those regions such as South Africa wherein dangerous variants of SARS-CoV-2 have swept the country.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we have previously shown that the hAd5 S-Fusion + N-ETSD vaccine elicits T helper cell 1 (Th1) dominant antibody responses to both S and N as well as T-cell activation after vaccination of a murine (CD1) pre-clinical animal model (5). We have also shown that the SARS-CoV-2 antigens expressed by the hAd5 S-Fusion + N-ETSD construct are recognized by T cells from previously SARS-CoV-2 infected individuals when expressed by autologous monocytederived dendritic cells (6). These studies provide evidence that vaccination with the hAd5 S-Fusion + N-ETSD vaccine (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…The hAd5 S-Fusion + N-ETSD vaccine we utilized the hAd5 [E1-, E2b-, E3-] comprises a wildtype spike (S) sequence [accession number YP009724390] modified with a proprietary linker peptide sequence as well as a wildtype nucleocapsid (N) sequence [accession number YP009724397] with a an Enhanced T-cell Stimulation Domain (ETSD) signal sequence to direct translated N to the endosomal/lysosomal pathway. 2 The SARS-CoV-2 S protein is found on the viral surface 11 and the N protein is found in the interior of the virus 23,56 (Fig. S1B).…”
Section: Supplementary Informationmentioning
confidence: 99%
“…The vaccine comprises the SARS-CoV-2 spike (S) protein optimized for cell surface expression (S-Fusion) 1 to increase humoral responses and the nucleocapsid protein with an Enhanced T-cell Stimulation Domain (N-ETSD) to target N to the endosomal/lysosomal cellular compartment to enhance MHC I and II presentation. 2…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation